SAFETY AGAINST SLIPS AND ANALYSIS OF TWO-SIDE SELFTIGHTENING CABLE CONNECTION DEVICES FOR EXTRACTION VESSELS - Iosif Dumitrescu,; Răzvan Bogdan Itu; Vilhelm Itu, (Fiabilitate şi Durabilitate)
Winding installations have the role of transporting, between underground and surface, useful minerals, materials, equipment, and people, with extraction vessels. Cable connecting devices connect winding installation cables to extraction vessels. Depending on their design, connecting cables can be: with loop and core, self-tightening with wedged core on one or both sides; with hinged jaw; with cone-shaped friction wedges; with wedges and bridles. The paper presents an analysis of circular self-tightening metal cable connecting devices wedged on both sides, meeting the requirements of STAS 12519/87.